The search for a meaningful past - Staloff, Darren 1961-; Teaching Company (Springfield, VA Teaching Co., 1995)
Presents lectures concerning the philosophical foundations of human history.
pt. 1. lecture 1. Issues and problems ; lecture 2. Mircea Eliade's Cosmos and history and cyclical time ; lecture 3. The early enlightenment and the search for the laws of history, Vico's New science of history ; lecture 4. The high enlightenment's cult of progress, Kant's idea for a universal history from a cosmopolitan point of view ; lecture 5. Hegel's philosophy of history ; lecture 6. Marx's historical materialism ; lecture 7. Nietzche's critique of historical consciousness, On the advantages and disadvantages of history for life ; lecture 8. Weber's historical sociology -- pt. 2. lecture 9. Taking the long view, Arnold Toynbee and world historical speculation ; lecture 10. Twentieth-century neo-idealism, R.G. Collingwood's The idea of history ; lecture 11. The positivist conception of historical knowledge, Carl Hempel's The function of general laws in history ; lecture 12. Analytic musings, Arthur Danto's Narration and knowledge ; lecture 13. Social history, structuralism, and the long duree, Fernand Brandel's On history ; lecture 14. Post-structuralism and the linguistic turn, Hayden White's Introduction to metahistory ; lecture 15. Naturalism revisited, William McNeill's Plagues and peoples ; lecture 16. The heterogeneity of historical understanding.
Teaching Co.: 425A--426A.
In two containers (26 cm.).
Keywords: History -- Philosophy